Comparison of different regimens of pimecrolimus 1% cream in the treatment of facial seborrheic dermatitis. (7th June 2017) - Zhao, Juemin; Sun, Wenjia; Zhang, Chengfeng; Wu, Jiaqiang; Le, Yan; Huang, Chunyun; Liu, Ye; Xiang, Leihong
Summary: Background: Pimecrolimus 1% cream has already been proved to be an effective and safe alternative to treat seborrheic dermatitis. However, the treatment periods were inconstant in previous studies. Objective: To evaluate the comparative efficacy of pimecrolimus 1% cream with different regimens for the treatment of facial seborrheic dermatitis. Method: Thirty patients with facial seborrheic dermatitis were enrolled and randomly distributed to three groups. Patients of Group 1 were treated with topical pimecrolimus cream 1% twice daily for 2 weeks and then a moisturizer cream twice daily for 2 weeks. Patients of Group 2 were treated with pimecrolimus cream 1% twice daily for 2 weeks and then once daily for another 2 weeks. Patients of Group 3 had a consecutive course of pimecrolimus cream 1% twice daily for 4 weeks. Objective symptoms, subjective symptoms, and dermatology life quality index (DLQI) were measured at weeks 0, 2, 4, and 6. Results: At week 4, the clinical severity scores of all three regimens significantly decreased ( P <.01). The improvement of total severity score in Group 3 was more remarkable than groups 1 and 2 (both P <.05). This effect was maintained until the end of the study in Group 3. Life quality of all three groups was significantly improved at week 4 ( P <.001), while there was no statistical difference on the improvement of life quality among three groups. Conclusion: We recommend pimecrolimus 1% cream could be applied twice a day for 4 weeks to treat seborrheic dermatitis.